Investigating the key attributes to enhance students' learning experience in 21st century class environment - Leow, Fui-Theng; Neo, Mai; Hew, Soon Hin (Academic Conferences and Publishing International (ACPI), 2016)
The 21st century marks the beginning of digital age with the extensive use of digital media, mobile devices, and Internet resources. Recent studies found that this digital era has expanded the landscape of student experiences, and educational technologies as well as increased the educator’s awareness on embracing technologies to promote effective learning. This has redefined the meaning of effective learning and the approaches in motivating students. Therefore, redesigning the learning environments plays an important role in enhancing the students’ experiences in the university classrooms. In this study, the 21st century class environment is designed by mapping Jonassen’s model and Gagne’s events to employ the constructivist learning approach, organize the information processing, and design the instructions to support effective learning. In order to study student’s perception in the 21st century class environment, this study employed the mixed methods approach, includes conducting exploratory factor analysis on the questionnaire response and the qualitative analysis on students’ comments. The research samples were formed by 300 undergraduate degree students who studied at INTI International University, Malaysia. The exploratory factor analysis has identified four main factors, group learning, motivation, skills development and knowledge transfer. In the discussion, this study presents the key attributes, the main contributors to the attributes and its impact on student learning. For instance, the factor of group learning can be stimulated by emphasizing on the identified key attributes, such as improved work relationship, improved leadership, and refined collaborative learning which enhancing student learning experience as they are keen to attempt different approach, and anticipate changes. This study aims to identify the factors and elaborate the key attributes for supporting the strategies in transforming the university class environment to enhances students’ learning experiences and promote effective learning.